2021
DOI: 10.1002/smll.202106271
|View full text |Cite
|
Sign up to set email alerts
|

Shape Engineering of TiO2 Microrobots for “On‐the‐Fly” Optical Brake

Abstract: the experiments, 5 µL of ultrapure water (18 MΩ cm) containing the microrobots was dropped on a glass slide, followed by the addition of H 2 O 2 solution. After recording videos of the microrobots at 20 fps without/with UV irradiation, NIS-Elements Advanced Research software was used to calculate the average speed values.Research data are not shared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…The continuous Pt coating on the flat side of the MXene-derived TiO 2 microparticle produces more H 2 compared to the discontinuous Pt coating on the multi-layered side, reflecting a larger H + concentration gradient and, so, a higher speed and 3D motion ability. This conclusion is consistent with the previously reported stronger propulsion for microrobots coated by a continuous Pt layer 27 , 53 , 54 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The continuous Pt coating on the flat side of the MXene-derived TiO 2 microparticle produces more H 2 compared to the discontinuous Pt coating on the multi-layered side, reflecting a larger H + concentration gradient and, so, a higher speed and 3D motion ability. This conclusion is consistent with the previously reported stronger propulsion for microrobots coated by a continuous Pt layer 27 , 53 , 54 .…”
Section: Resultssupporting
confidence: 93%
“…In fact, for UV-light-powered Pt/ZnO Janus micromotors, it has been demonstrated that a smooth ZnO microparticle results in a continuous Pt coating and the fuel-free motion ability, while a rough ZnO microparticle leads to a discontinuous Pt coating which requires H 2 O 2 fuel for the autonomous propulsion 27 . Similarly, smooth TiO 2 microparticles coated by a continuous Pt layer exhibited a higher speed under UV-light-irradiation in H 2 O 2 than rough ones 53 . Moreover, it has been shown that transforming a continuous Pt film on SiO 2 microspheres into discrete Pt nanoparticles via thermal annealing causes an ~80% decrease in their self-electrophoretic speed due to the lower electric field or fluid flow generated by the discontinuous Pt coating 54 .…”
Section: Resultsmentioning
confidence: 91%
“…[11,22] In these conditions, the photocatalytic ability of B-TiO 2 to produce radicals and chemical species onto its surface is intensely improved, and the photogenerated electrons can oxidize H ) while reduction of protons and H 2 O 2 occurs at the metal side. [11,15,29,31,34,43] Contemporarily, H 2 O 2 and protons are reduced to water at the Ag side. The resulting gradient establishes a local electric field which causes the nanorobots to propel via the self-electrophoretic mechanism.…”
Section: Fabrication Characterization and Motion Analysis Of B-tio 2 ...mentioning
confidence: 99%
“…Among them, photocatalytic nanorobots are of particular interest since their motion can be controlled by irradiation or adjusting the incident light. [29][30][31][32][33] They also possess the ability to generate and release reactive oxygen species (ROS) capable of initiating photodegradation processes for improved therapeutic outcomes. [18,34] Recently, significant attention has also been devoted toward nanorobots that can be actuated by any portion of the available light spectrum to adapt them to the specific application.…”
Section: Introductionmentioning
confidence: 99%
“…Light-driven motion is primarily attractive for water remediation with photocatalytic semiconductors. [24][25][26][27] Enzymatic micro/nanorobots are more appropriate for biomedical applications but are limited to human body regions where a specific biomolecule is available. [28] Instead, magnetic manipulation offers high precision in the whole body without fuels.…”
Section: Introductionmentioning
confidence: 99%